Outcomes from treatment of metastatic renal-cell carcinoma following failure of first-line anti-VEGF/VEGFR therapy: real-life evidence on the change of the treatment paradigm. Issue 3 (16th November 2022) - Bamias, Aristotelis; Zakopoulou, Roubini; Tzannis, Kimon; Sakellakis, Minas; Koutsoukos, Konstantinos; Kyriazoglou, Anastasios; Panagiotou, Aikaterini; Armylagos, Stylianos; Rokas, Konstantinos; Gotzias, Dimitrios; Boulouta, Anna; Bozionelou, Vassiliki; et al.
Abstract : Recently approved agents for post-vascular endothelial growth factor/post-vascular endothelial growth factor receptor (VEGF/VEGFR) inhibitors treatment of metastatic renal-cell carcinomas (mRCC), such as axitinib, nivolumab, and cabozantinib were shown to improve prognosis and substituted everolimus in this setting. We studied practice patterns, efficacy, and tolerability of these agents in a real-world series of Greek patients. We included patients with mRCC who received everolimus, axitinib, or nivolumab after progression on first-line anti-VEGF/VEGFRs therapy. Patients were stratified into three groups. Group A received nivolumab with or without cabozantinib at some point in their disease. Group B received axitinib but without nivolumab or cabozantinib. Group C received only everolimus among the four approved agents. Overall, 131 patients were included in the analysis. Everolimus and nivolumab were mainly used in the second line, while axitinib and cabozantinib were mostly used in the third and fourth lines. Median overall survival (OS) from first-line initiation was 8.7 [95% confidence interval (CI), 4–not reached], 3.6 (95% CI, 2–6), and 2.1 years (95% CI, 1.4–2.6) for Group A, B, and C, respectively ( P  < 0.001). Median OS from the initiation of second-line therapy was 3.5, 2.7, and 1.3 years, respectively ( P  < 0.001). There was no impact of first-line agent or treatment timing on survival. International Metastatic Renal Cell Carcinoma Database Consortium risk stratification was associated with OS. Toxicities observed were within expected frequencies. Grade ≥3 events were rare. Adoption of modern standards in everyday treatment of mRCC results in prolongation of survival. Real-world datasets are the new landmarks of survival for future research.